2022
DOI: 10.1186/s13048-022-01018-9
|View full text |Cite
|
Sign up to set email alerts
|

The presence of living endometrial cells in ovarian endometriotic cyst fluid may contribute to the recurrence of endometriosis after surgical excision of endometriomas

Abstract: Background Many factors can affect the recurrence of endometriosis after surgery, however, whether endometriotic cyst fluid contributes to endometriosis recurrence after surgical excision of ovarian endometriomas remains unclear. The objective of this study was to determine the presence of endometrial cells in ovarian endometriosis cyst fluid and the potential differences between these cells and those in the cyst wall. Methods Samples of cyst fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…A recent study suggested that the presence of living endometrial cells in ovarian endometriotic cyst fluid may contribute to the recurrence of endometriosis after surgical excision of OMAs [ 13 ]. We recommend that adhesiolysis (which requires excellent vision) is more easily performed with the OMA intact (rather than deflated); however, the risk of rupturing the pathology during adhesiolysis needs to be balanced.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the presence of living endometrial cells in ovarian endometriotic cyst fluid may contribute to the recurrence of endometriosis after surgical excision of OMAs [ 13 ]. We recommend that adhesiolysis (which requires excellent vision) is more easily performed with the OMA intact (rather than deflated); however, the risk of rupturing the pathology during adhesiolysis needs to be balanced.…”
Section: Discussionmentioning
confidence: 99%
“…All types of endometriotic lesions have a high rate of recurrence after conservative surgery. It has been proposed that recurrence rates of endometriosis after surgery occur due to cyst fluid leakage of ovarian endometriotic cyst fluid, which contains living endometrial cells with high adhesion ability, which may contribute to the recurrence of endometriosis after surgical excision [60]. This poses a significant further strain on the management of endometriosis.…”
Section: Surgical Techniques That May Help To Reduce Ovarian Damage I...mentioning
confidence: 99%
“…An ovarian cyst, a common tumor of the female reproductive system, is caused by an abnormal endocrine system or genetic factors ( 1 , 2 ). It has an incidence rate of 1.3–24.0%, with more than 90% being benign tumors ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%